A Cross-sectional study to analyse the anthropometric measurements of mental foramen of dry human mandibles - Awan, Jawaria Aslam; Surti, ambreen; Naz, Ayesha Saba; Qamar, Aisha; Ahmed, Rashid (ADVANCES IN BASIC MEDICAL SCIENCES, 2023)
Objective To observe shape, size and position of “mental foramen” in association with clinically relevant landmarks of mandible. Methodology The distance from different landmarks such as mandibular symphysis, crest of the alveolar bone, ramus of mandible (posterior border) and mandibular base were measured with the help of a digital Vernier caliper for calculating mental foramen’s size. Each measurement was taken 3 times with an interval of 3 days. Pearson’s correlation was used to observe association between measurements of “mental foramen.” Results Frequently occurring shape of “mental foramina” was “oval”. Commonest position was found as position IV (50%), where it was present on an axis passing longitudinally through the 2nd premolar. Weak positive correlation was observed on right side between vertical diameter (VD) as well as Horizontal diameter (HD), however, weak negative correlation was noted between the VD and HD on the left side. But a positive correlation was also seen in the VD and HD. Conclusions There are variations in shape and size, as well as position of “mental foramen” in our community. Knowledge in regards to these variations is essential for accurate localization of mental foramen which in turn is important both in forensic medicine as well as in clinical application.